Drumstick Cultivation - A Success Story - Shankar, Adhi; Reddy, T. Prabhakar; Rajashekhar, B.; Rajashekhar, M.; Ramakrishna, K.; Jahan, Afifa (Chronicle of Bioresource Management, 2021)
Cotton is the major crop in Nagarkurnool district accounting for 62% of total cropped area. Cotton is a highly input and labour intensive crop, but, fetch low net profit ranging from Rs. 25,000-50,000 ha-1. The KVK, Palem has introduced the drumstick crop and popularized the PKM-1 variety during 2018 to 2020 through front line demonstrations (FLDs). Drumstick (Moringa oleifera Lam.), family Moringaceae, is a softwood tree, popular for its tender pods, leaves and flowers. The pod is used as a vegetable in Indian cuisine for its flavor and nutritional value. The commercial cultivation of drumstick has been increased and became profitable after the availability of annual variety PKM-1. The drumstick farm is easy to maintain and effective due to less operational maintenance and expenses as compared to that of cotton crop. As a result, it’s cultivation had increased to 20 ha under PKM-1 variety in the district. A success story has been presented here which inspired fellow farmers in the district.